2020
DOI: 10.3389/fphys.2020.00716
|View full text |Cite
|
Sign up to set email alerts
|

Ground-Based Analogs for Human Spaceflight

Abstract: This mini-review provides an updated summary of various analogs for adaptations of humans to the microgravity of space. Microgravity analogs discussed in this paper include dry immersion, wet immersion, unilateral lower-extremity limb suspension, head down tilt (HDT), and supine bed rest. All Earth-based analogs are imperfect simulations of microgravity with their own advantages and disadvantages. This paper compares these five frequently used microgravity analogs to offer insights into their usefulness for va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 24 publications
2
57
0
Order By: Relevance
“…Using this method, a relatively large number of studies performed under real and simulated microgravity conditions has been carried out ( Lee et al, 2014 ; Schneider et al, 2015 ; Treffel et al, 2016 ; de Abreu et al, 2017 ; Rukavishnikov et al, 2017 ; Schoenrock et al, 2018 ). The Dry Immersion (DI) model is used less often than the bed rest model, but it reproduces neuromuscular deconditioning quite accurately ( Navasiolava et al, 2011 ; Watenpaugh, 2016 ; Tomilovskaya et al, 2019 ; Pandiarajan and Hargens, 2020 ). All studies, even with short exposures such as parabolic flight or several hours of DI, have shown a decrease in muscle tone.…”
Section: Introductionmentioning
confidence: 99%
“…Using this method, a relatively large number of studies performed under real and simulated microgravity conditions has been carried out ( Lee et al, 2014 ; Schneider et al, 2015 ; Treffel et al, 2016 ; de Abreu et al, 2017 ; Rukavishnikov et al, 2017 ; Schoenrock et al, 2018 ). The Dry Immersion (DI) model is used less often than the bed rest model, but it reproduces neuromuscular deconditioning quite accurately ( Navasiolava et al, 2011 ; Watenpaugh, 2016 ; Tomilovskaya et al, 2019 ; Pandiarajan and Hargens, 2020 ). All studies, even with short exposures such as parabolic flight or several hours of DI, have shown a decrease in muscle tone.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that in a short time, within 3–7 days, there is a change in the sensorimotor functions: a decrease in accuracy of movement control, decline in the accuracy of visual tracking, and an increased sensitivity to vestibular signals. The physiological aspects of these models, obtained from participation of male volunteers, are described in details in the review articles ( Pavy-Le Traon et al, 2007 ; Navasiolava et al, 2011 ; Watenpaugh, 2016 ; Tomilovskaya et al, 2019 ; Pandiarajan and Hargens, 2020 ). However, studies involving this model in women have never been conducted, in part, due to a number of hygienic and physiological difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial-based analogs for LDSF have been of longstanding interest in space medicine research as simulated microgravity is an efficient platform to observe physiology in extreme situations. Analogs such as supine bed rest, head-down tilt bed rest (HDTBR), wet immersion, dry immersion, and lower-extremity limb suspension have been previously applied as earthbound experimental models to further understand the human body during spaceflight (24). HDTBR studies serve as a terrestrial analog by altering the vector of gravitational force on the body to generate a cephalad fluid shift similar to that seen in microgravity (43)(44)(45).…”
Section: Head-down Tilt Bed Rest Studies and Clinical Findingsmentioning
confidence: 99%
“…Though other techniques such as parabolic flight more closely simulate the actual microgravity condition, the brief duration of exposure is not sufficient for manifestation of SANS-like features. In contrast, long-duration HDTBR is feasible with study durations of 370 days having been successfully completed ( 24 , 47 ). Furthermore, many outcomes analogous to those used by NASA for study of astronauts (MRI, OCT, LP etc.)…”
Section: Head-down Tilt Bed Rest Studies and Clinical Findingsmentioning
confidence: 99%